1999
DOI: 10.1038/sj.bjc.6690137
|View full text |Cite
|
Sign up to set email alerts
|

The influence on survival of delay in the presentation and treatment of symptomatic breast cancer

Abstract: SummaryThe aim of this study was to examine the possible influence on survival of delays prior to presentation and/or treatment among women with breast cancer. Duration of symptoms prior to hospital referral was recorded for 2964 women who presented with any stage of breast cancer to Guy's Hospital between 1975 and. Median follow-up is 12.5 years. The impact of delay (defined as having symptoms for 12 or more weeks) on survival was measured from the date of diagnosis and from the date when the patient first no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
2
5

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(190 citation statements)
references
References 31 publications
11
168
2
5
Order By: Relevance
“…Richards and colleagues (1999) showed that marked delays between the onset of symptoms and the initiation of treatment were associated with lower survival rates. 33 Consistent with our results, Smith and colleagues found that the association between total time and survival was not statistically significant (HR=1.00; 95%CI 0.99-1.00). 9 In Mexico, two studies have estimated this delay but not its association with survival.…”
Section: Total Timesupporting
confidence: 81%
“…Richards and colleagues (1999) showed that marked delays between the onset of symptoms and the initiation of treatment were associated with lower survival rates. 33 Consistent with our results, Smith and colleagues found that the association between total time and survival was not statistically significant (HR=1.00; 95%CI 0.99-1.00). 9 In Mexico, two studies have estimated this delay but not its association with survival.…”
Section: Total Timesupporting
confidence: 81%
“…[1] However, the evidence supporting a link between delay in diagnosis and poorer cancer outcome is weak. [14][15][16][17][18][19][20][21][22][23][24][25] The greatest number of studies examining diagnostic delays have been in patients with breast…”
Section: Delays In Diagnosismentioning
confidence: 99%
“…The length of symptom duration commonly used to indicate this delay is more than 3 months (Burgess et al, 1998;Montazeri et al, 2003;Friedman et al, 2006). This categorisation is based on the evidence that patients who delay presentation for 3 months or more have lower 5-year survival rates than those with less delay (Richards et al, 1999).…”
Section: Introductionmentioning
confidence: 99%